Statistik dan Peranannya Dalam Pembangunan Nasional - Sang Saniaka Tajulfitri (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
Statistics have an important role in planning, implementing, monitoring, and evaluating the implementation of various activities in all aspects of community, national and state life in national development. The increasing need and variety of information that develops along with the advancement of national life, science and technology, and the increasing demand for data by government agencies both at the center and in the regions, private institutions, and the public make statistics as indispensable information. Therefore, the Central Bureau of Statistics, which is the organizer of basic statistics, must implement national policies in the field of statistics by paying attention to the aspirations, needs, and participation of statistical users so that the statistical results are expected to be utilized to the benefit of the government and society. Law No. 16 of 1997 concerning Statistics, Government Regulation Number 51 of 1999 concerning Statistic Administration and Presidential Regulation No. 51 of 1999 concerning BPS)